2013
DOI: 10.1089/ten.tec.2012.0616
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids Regulate Epithelial–Stromal Cell Cross Talk and Trophoblast Attachment Invasion in a Three-Dimensional Human Endometrial Culture System

Abstract: Human embryo implantation involves a complex network of molecular signaling that is modulated by endocrine and paracrine pathways. Here, we performed studies using a unique and recently developed three-dimensional (3D) implantation model, characterized by an endometrium-like 3D culture system and Jar cell-derived spheroids mimicking the embryo/trophoblast. The aims were to investigate the effects of 17β estradiol (E2) and medroxyprogesterone acetate (MPA) on (1) the interaction between epithelial and stromal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…JAr spheroids represent an appropriate embryo-like model for studies mimicking implantation [17]. We found that JAr cells expressed AQP3 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…JAr spheroids represent an appropriate embryo-like model for studies mimicking implantation [17]. We found that JAr cells expressed AQP3 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Ishikawa cells derived from endometrial adenocarcinoma and T-HESCs established from primary HESCs by telomerase immortalization are well accepted for in vitro studies of human endometrium (17)(18)(19)(20). Specifically, both cell lines share similar biochemical properties with primary endometrial cells when induced by ovarian steroids and cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, defining an appropriate ECM hydrogel for engineering mucosal barrier tissues for extended in vitro culture and function is an ongoing challenge. In epithelial monocultures, the basement membrane extract Matrigel™ is commonly used, 13,14 whereas type I collagen gels or fibrin gels are used as representative microenvironments for stromal cells, 1517 with no single composition ideal for both cell types in co-culture. Further, although these and other natural ECM gels are readily available commercially, they exhibit substantial inherent batch-to-batch variability, variations in growth factor composition depending on preparation method, limited opportunity to tailor matrix degradation or signaling properties, and are difficult to microfabricate for organs-on-chips type applications.…”
Section: Introductionmentioning
confidence: 99%